Analisis Kinerja Keuangan Dengan Metode Economic Value Added (EVA), Market Value Added (MVA), dan Financial Value Added (FVA) - Rahmah Arafati Masyiyan (Universitas Islam Bandung, 2019)
EVA, MVA, and FVA analysis techniques are used to see better and more efficient financial performance of the company. This study aims to determine financial performance based on EVA (Economic Value Added) method, Market Value Added, and Financial Value Added in coal mining sub-sector companies listed on the Indonesia Stock Exchange. This study uses a descriptive quantitative method, with a purposive sampling technique in the coal subsector mining companies listed on the Stock Exchange and posting operating profit for the period 2014-2018.EVA results in this study are 6 companies with stock codes BYAN, DOID, ITMG, PTBA, SMMT, and TOBA which have positive EVA values over a period of 5 years. Then from this study there are MVA results that tend to be negative. There are 3 companies with stock codes DOID, ITMG, and PTRO that have negative MVA values each year for a period of 5 years. Then for the FVA value generated in this study, there are 3 companies that have negative FVA values each year during the study period, those companies are companies with stock codes DOID, KKGI, and PTRO.